Patients with resistant arterial hypertension: options of the daily blood pressure profile - Kulbachuk, O. S.; Sid, Eu. V.; Soloviov, O. V.; Piskun, A. V.; Кульбачук, Олександр Сергійович; Сідь, Євген Володимирович; Соловйов, Олександр Володимирович; Піскун, Анастасія Вадимівна (My University, 2024)
The purpose of the study: to determine the types of daily profile of blood pressure in patients with resistant arterial hypertension.